2024
DOI: 10.1093/molbev/msae010
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Together: Cassandra Retrotransposons Gradually Mirror Promoter Mutations of the 5S rRNA Genes

Sophie Maiwald,
Ludwig Mann,
Sònia Garcia
et al.

Abstract: The 5S rRNA genes are among the most conserved nucleotide sequences across all species. Similar to the 5S preservation we observe the occurrence of 5S-related nonautonomous retrotransposons, so-called Cassandras. Cassandras harbor highly conserved 5S rDNA-related sequences within their long terminal repeats, advantageously providing them with the 5S internal promoter. However, the dynamics of Cassandra retrotransposon evolution in the context of 5S rRNA gene sequence information and structural arrangement are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…For example, so-called Cassandras, the 5S-related nonautonomous retrotransposons in plants, harbor highly conserved 5S rDNA sequences within their long terminal repeats [ 30 ]. Moreover, recent work has shown evidence for a gradual coevolution of Cassandra transposons with their corresponding 5S rDNAs [ 11 ]. However, the organization of 5S rDNA clusters in T. freemani is, as far as we know, the first example of 5S rRNA genes being associated with two types of the most abundant repetitive sequences, satDNA and TE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, so-called Cassandras, the 5S-related nonautonomous retrotransposons in plants, harbor highly conserved 5S rDNA sequences within their long terminal repeats [ 30 ]. Moreover, recent work has shown evidence for a gradual coevolution of Cassandra transposons with their corresponding 5S rDNAs [ 11 ]. However, the organization of 5S rDNA clusters in T. freemani is, as far as we know, the first example of 5S rRNA genes being associated with two types of the most abundant repetitive sequences, satDNA and TE.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequence of Mutsu retrotransposons is approximately 5500 bp long and consists of two open reading frames (ORFs) flanked by untranslated regions (UTRs). Recent evidence has shown the occurrence of 5S-related nonautonomous retrotransposons, so-called Cassandras, in plants [ 11 ]. Cassandras harbor highly conserved 5S rDNA-related sequences within their long terminal repeats.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no 5S-derived SINEs in plants. Instead, plants harbor non-autonomous LTR retrotransposons with 5S rDNA promoter sequences in their LTRs, named Cassandra ( Kalendar et al 2008 , 2020 ; Maiwald et al 2021 , 2024 ; a recent study also found analogous retrotranspons in ribbon worms, named Ajax ( Kojima 2024 )). Cassandras were first described in 50 plant species including ferns, monocots, and eudicots and later (re)confirmed in several angiosperm lineages ( Yin et al 2014 ; Gao et al 2016 ; Kalendar et al 2020 ), including Arabidopsis ( Sampath and Yang 2014 ), Agave ( Tamayo-Ordóñez et al 2018 ), and beets ( Maiwald et al 2021 ).…”
Section: Ribosomal Dna In Tesmentioning
confidence: 99%
“…At present, there are no reports of Cassandras in gymnosperms. Looking closely at the Asteraceae, the plant family with most variability in the 5S rDNA, including rDNA arrangements ( Garcia et al 2010 ) and promoter shifts ( Garcia et al 2012 ), Maiwald et al (2024) found that Cassandra retrotransposons closely mimic the promoter motif changes, thus providing a recent example of rDNA–TE co-evolution.…”
Section: Ribosomal Dna In Tesmentioning
confidence: 99%